Melatonin’s Role in Female Fertility: Molecular Insights and Therapeutic Implications - Saraswati, Benedikta Diah (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2025)
Background: This narrative review examines how melatonin enhances reproductive health functions. Melatonin has established itself as a multifaceted neurohormone with pivotal roles in female reproductive health. Through its potent antioxidant properties, melatonin protects oocytes and orchestrates hormonal regulation and ovarian function, with melatonin receptors strategically located in key reproductive tissues, including ovarian granulosa and luteal cells. Method: This narrative review examines how melatonin preserves and enhances female fertility by analyzing clinical outcomes and molecular pathways. It compiles research on the effects of melatonin on ovarian function, oocyte quality, hormone regulation, and assisted reproductive technologies from major databases published between 2015 and 2025. The study consistently shows how melatonin works and its potential benefits, offering broad insights without strict limits. Result: Melatonin operates through multiple receptor-mediated pathways to regulate reproductive functions. Clinical evidence shows melatonin supplementation improves assisted reproductive technology (ART)’s success rates by enhancing oocyte maturation and embryo quality, restoring menstrual regularity in PCOS patients, and protecting reproductive tissues from oxidative stress-induced damage. Implication: These findings support melatonin's therapeutic potential in assisted reproductive technologies and treating reproductive disorders. Healthcare providers should consider melatonin supplementation as an adjuvant therapy for women undergoing fertility treatments or experiencing reproductive dysfunction while establishing standardized protocols for optimal dosing and timing. Novelty: This comprehensive review reveals melatonin's multifaceted role as a fertility regulator, providing molecular insights into its therapeutic mechanisms and clinical applications in women's reproductive health across the reproductive lifespan